A "Failed" Assay Development for the Discovery of Rescuing Small Molecules from the Radiation Damage. (December 2021) - Wen, Kuo-Kuang; Roy, Stephen; Grumbach, Isabella M.; Wu, Meng
With improving survival rates for cancer patients, the side effects of radiation therapy, especially for pediatric or more sensitive adult patients, have raised interest in preventive or rescue treatment to overcome the detrimental effects of efficient radiation therapies. For the discovery of rescuing small molecules for radiation damage to the endothelium, we have been developing a 96-well microplate-based in vitro assay for high-throughput compatible measurement of radiation-induced cell damage and its rescue by phenotypic high-content imaging. In contrast to traditional radiation assays with detached cells for clonogenic formation, we observed cells with live-cell imaging in two different kinds of endothelial cells, up to three different cell densities, two gamma-infrared radiation dose rates, more than four different radiation doses, and acute (within 24 h with one to two h intervals) and chronic (up to 7 days) responses by phenotypic changes (digital phase contrast) and functional assays (nuclear, live-cell, and dead-cell staining) at the end of the assay. Multiple potential small molecules, which have been reported for rescuing radiation damage, have been tested as assay controls with dose responses. At the end, we did not move ahead with the pilot screening. The lessons learned from this "failed" assay development are shared.